Information Campaigns / Balancing Social Values and Social Change - Salmon T. Charles (Sage Publications)
Preface, Acknowledgements, Campaigns and Social Structure, The Campaign Process, About the Contributors.
Preface, Acknowledgements, Campaigns and Social Structure, The Campaign Process, About the Contributors.